"Earthly Angels"? A qualitative study of the domiciliary care worker role in meeting the needs of families caring for those dying at home. Issue 6 (21st October 2013) - Percival, John; Lasseter, Gemma; Purdy, Sarah; Wye, Lesley
Abstract: Objective: Relatively little attention has been paid to optimum ways in which community-based care services can support family caregivers in the context of end-of-life care at home. This paper addresses such concerns by focusing on the services provided by domiciliary care workers. Method: We draw on qualitative formal interviews with 42 family members, 1 patient, and 6 staff, as well as observation sessions and informal interviews with additional family caregivers and staff, to examine the aspects of domiciliary care perceived to be of most value. In particular, we compare and contrast family caregivers' experience of the support provided by generic domiciliary care workers with that of a team of specialist domiciliary care workers. Results: Our findings show that specialist domiciliary care workers had sufficient time and expertise to meet family caregivers' physical and emotional needs in sensitive, proactive, and family-centered ways, and that these attributes were not so prominent in the services received from generic domiciliary care workers. Significance of results: The availability to families of targeted support from an appropriately trained and carefully monitored team of specialist domiciliary care workers, able to operate flexibly and with staff consistency, appears to be an important foundation on which to build greater confidence in the reality of a good death at home.